Disrupting the PCSK9/LDLR protein–protein interaction by an imidazole-based minimalist peptidomimetic. Issue 41 (6th October 2016) - Stucchi, Mattia; Grazioso, Giovanni; Lammi, Carmen; Manara, Silvia; Zanoni, Chiara; Arnoldi, Anna; Lesma, Giordano; Silvani, Alessandra
Abstract : We report on a tetraimidazole-based β-strand minimalist peptidomimetic as a novel inhibitor of LDLR–PCSK9 protein–protein interaction, a promising target for hypercholesterolemia. Abstract : Herein we report on the multicomponent synthesis of a novel imidazole-based compound, able to act efficiently as a minimalist β-strand mimic. Biological evaluation proved its ability to impair the LDLR–PCSK9 protein–protein interaction, disclosing it as the first small molecule exerting a PCSK9-mediated hypocholesterolemic effect.